Tourist Satisfaction at Beach Shacks: Case Study Analysis - Mario Barretto, Helic; R. , Antony Sathish Benadict (International Journal of Psychosocial Rehabilitation, 2020)
Tourists normally are not interested in staying in boring hotels because they want to explore the unknown around the world. In Goa, tourists prefer to stay in shacks as they offer excellent service and give a unique experience. Shacks in Goa are seasonal structures erected close to the beach. The present study intends to identify the services offered by beach shacks to the tourists that contribute to their satisfaction. The study is quantitative in nature, based on a random sample of 400 tourists, including 200 foreign nationals. The data was collected during the months of October to December 2019 using a structured questionnaire. Using Exploratory Factor Analysis and Structural Equation Model, the findings indicate that the personalized services, leisure services, and convenience services significantly contribute to the satisfaction of tourists visiting beach shacks in Goa.